Doing water research differently for innovation in regional water productivity in Australia. Issue 1 (2nd January 2016) - Ayre, Margaret; Nettle, Ruth; Erazo Bobenrieth, Manuela; Klerkx, Laurens
Abstract: Research in innovation studies suggests that appropriate starting conditions are required if alignment of research to practice and policy is to be enabled. To achieve this alignment, a scoping exercise is required and must involve those people and institutions that have an interest in the research. This paper describes a consultation process to develop a Blueprint for Regional Water Productivity in Australia through a new research initiative at the University of Melbourne. This Blueprint was developed through a two-stage consultation project in which opportunities and constraints for system innovation in regional water productivity in Australia were identified and discussed with key stakeholders without pre-empting research or development questions. In this paper, we ask: Did this consultation process constitute a platform for innovation in research practices? In addressing this question, we describe this process and suggest that it constituted a fledgling platform for innovation in research practices characterised by new social arrangements, material exchanges and the discursive object of `innovation systems'. However, the potential for institutional change from this platform will depend on continued deliberation between water sector actors in new routines of research-development practice, and collective action through the formalisation of new partnerships between researchers, practitioners and policy-makers.